THE ANALYSIS OF THE MODALITIES COMPARISON OF REGENT AND VICE REGENT CANDIDATES IN SIMULTANEOUS REGIONAL ELECTION 2017 IN JEPARA - Nadia Ajeng Triyanti; Turtiantoro . (Journal of Politic and Government Studies, 2018)
The victory of a pair supported by a single party over another pair supported by 9 parties in the regional election in Jepara district is the background of this research. The problem statement of this research is “How is the modalities comparison possessed by the regent and vice regent candidates in the regional election 2017 in Jepara district?”The objectives of this research are to determine the modality possessed by the two pairs of regent and vice regent candidates in the simultaneous regional election 2017 in Jepara district and what modal becomes the victory factor from the pair having more votes.The effort to answer the problems and the research objectives is done by using modality theory, consisting of political capital, social capital, and economic capital which were then analysed by using descriptive method. The regent and vice regent candidates also the supporting parties are the objects of this research.The result of the research shows that the pair having more votes is Ahmad Marzuqi and Dian Kristiandi who have higher social capital compared to the other pairs and beat its competitor which is Subroto and Nur Yahman who have stronger political and economic capital.It is suggested that each pair joining the political contest try harder to further utilize each capital among the three capitals possessed and accumulate them well. Because each capital is an important factor in determining the pair’s victory.Keywords: Pair, Regional Election, Modalities, Pair